A transformable gold nanocluster aggregate-based synergistic strategy for potentiated radiation/gene cancer therapy. Issue 9 (22nd February 2021) - Wu, Chun; Du, Xuancheng; Jia, Bingqing; Zhang, Chengmei; Li, Weifeng; Liu, Tian-Cai; Li, Yong-Qiang
Abstract : A transformable gold nanocluster aggregate-based synergistic strategy for a potentiated cancer radiation/gene therapy is presented. Abstract : Nano-radiosensitizers provide a powerful tool for cancer radiation therapy. However, their limited tumor retention/penetration and the inherent or adaptive radiation resistance of tumor cells hamper the clinical success of radiation therapy. Herein, we report a synergistic strategy for potentiated cancer radiation/gene therapy based on transformable gold nanocluster aggregates loaded with antisense oligonucleotide-targeting survivin mRNA (named AuNC-ASON). AuNC-ASON exhibited acidic pH-triggered structure splitting from a gold nanocluster aggregate (around 80 nm) to gold nanocluster (<2 nm), leading to the tumor microenvironment-responsive size transformation of the nano-radiosensitizer and activated release of the loaded antisense oligonucleotides to perform gene silencing. The in vitro experiments demonstrated that AuNC-ASON could amplify and improve the radio-sensitivity of tumor cells (the sensitization enhancement ratio was about 1.81) as a result of the synergistic effect of the transformable gold nanocluster radiosensitizer and survivin gene interference. Remarkably, the size transformation capability realized the high tumor retention/penetration and renal metabolism of AuNC-ASON in vivo and boosted the radio-susceptibility of cancer cells with the assistance of survivin gene interference, synergistically achieving potentiated tumor radiation/gene therapy. The proposed concept of transformable nano-radiosensitizer aggregate-based synergistic therapy can be utilized as a general strategy to guide the design of activatable multifunctional nanosystems for cancer theranostics.